2017
DOI: 10.1038/s41598-017-01893-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual homomorphism in dioecious trees: extensive tests fail to detect sexual dimorphism in Populus

Abstract: The evolution of sexual dimorphism and expansion of sex chromosomes are both driven through sexual conflict, arising from differing fitness optima between males and females. Here, we pair work in poplar (Populus) describing one of the smallest sex-determining regions known thus far in complex eukaryotes (~100 kbp) with comprehensive tests for sexual dimorphism using >1300 individuals from two Populus species and assessing 96 non-reproductive functional traits. Against expectation, we found sexual homomorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 69 publications
(114 reference statements)
3
46
0
Order By: Relevance
“…Although the non‐recombining SDR on Populus balsamifera chromosome 19 is small (McKown et al ., ), we found that there were a remarkably large number of genes exhibiting sex‐biased expression in flowers, indicating that the few genes in the SDR have an outsized effect on differences in gene expression between male and female flowers. Major categories of sex‐biased genes in flowers were associated with secondary sexual characters, such as energetic demands and defense against herbivores.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although the non‐recombining SDR on Populus balsamifera chromosome 19 is small (McKown et al ., ), we found that there were a remarkably large number of genes exhibiting sex‐biased expression in flowers, indicating that the few genes in the SDR have an outsized effect on differences in gene expression between male and female flowers. Major categories of sex‐biased genes in flowers were associated with secondary sexual characters, such as energetic demands and defense against herbivores.…”
Section: Discussionmentioning
confidence: 67%
“…In tissues sampled from the same stem, flowers showed sex‐biased expression in nearly one‐third of annotated genes, whereas leaves showed sex bias in only one gene. This low level of sex‐biased gene expression in leaves is consistent with findings from two recent studies that both provided strong evidence for the absence of sexual dimorphism in non‐floral tissues in the genus Populus , including P. balsamifera (Robinson et al ., ; McKown et al ., ). Because many vegetative characteristics are sexually homomorphic in P. balsamifera (McKown et al ., ), sexually dimorphic adaptations in vegetative characters may either be absent or isolated to specific environments or tissues not sampled in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ‘UBC’ collection was made by the British Columbia Ministry of Forests, Lands, Natural Resource Operations & Rural Development across the northern two‐thirds of the species’ range (44.0–59.6°N, 121.2–137.9°W). From this source, genotypes were planted in 2008 at Totem Field, Vancouver, BC (49.25°N, 123.10°W; McKown et al ., ) and in 2009–2010 at Agassiz, BC (49.25°N, 121.95°W; McKown et al ., ). The ‘GW/BESC’ collection originating from Oregon–Washington (44.5–48.9°N, 121.7–123.7°W) in the southern‐central portion of the species’ range was obtained from GreenWood Resources, Portland, OR, and the BioEnergy Science Center, Department of Energy, Oak Ridge, TN.…”
Section: Methodsmentioning
confidence: 97%
“…In addition, recent studies showed that poplar sex is genetically determined and only a small percentage of trees with recombination in the sex-associated genome region could change the sex (Geraldes et al, 2015;Borkhert et al, 2017;McKown et al, 2017). These data open up new opportunities for molecular marker development so as to use in the landscaping only male poplars, which do not produce fluff, while barcoding using ITS will allow evaluation of polymorphism and maintenance the diversity of populations adaptive to unfavorable urban conditions.…”
Section: Resultsmentioning
confidence: 99%